2022
DOI: 10.1016/j.jbc.2022.101581
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor GATA4 drives RNA polymerase III-directed transcription and transformed cell proliferation through a filamin A/GATA4/SP1 pathway

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Analysis of STAT3 and TP73 reads revealed that STAT3 silencing increased TP73 mRNA reads ( Figure 4G and H ). Interestingly, STAT3 expression in SaOS2 cells is also opposite to TP73 expression ( Figure 4—figure supplement 2 ) when gene expression is analyzed based on the RNA-seq data derived from SaOS2 FLNA-depleted cells ( Zhang et al, 2022 ). Collectively, these results suggest that STAT3 can negatively regulate TP73 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of STAT3 and TP73 reads revealed that STAT3 silencing increased TP73 mRNA reads ( Figure 4G and H ). Interestingly, STAT3 expression in SaOS2 cells is also opposite to TP73 expression ( Figure 4—figure supplement 2 ) when gene expression is analyzed based on the RNA-seq data derived from SaOS2 FLNA-depleted cells ( Zhang et al, 2022 ). Collectively, these results suggest that STAT3 can negatively regulate TP73 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Pol III subunit G (POLR3G) silencing inhibits the expression of a small non-coding RNA (snaR-A) that is related to cancer proliferation and metastasis, and POLR3G upregulation is associated with poor survival outcomes in several cancers ( Van Bortle et al, 2022 ). In the latest work, GATA4 has been shown to drive Pol III-directed transcription and cancer cell proliferation by enhancing the expression of SP1, which can directly activate the transcription of Brf1 and Gtf3c2 genes by binding to their promoters ( Peng et al, 2020 ; Zhang et al, 2022 ). Despite enormous advances in Pol III-dependent transcription, the mechanisms and factors governing this process remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…For one quantitative PCR (qPCR) reaction, 1 μL of cDNA samples was mixed with 0.5 μL of 5 μM forward and reverse primers and 10 μL of 2× SYBRGreen PCR Mastermix within a 2 0μL reaction system. Quantitative PCR reactions were performed in a Bio-Rad real-time detection system as described previously ( Zhang et al, 2022 ). An Actin gene was used as a reference gene, and GAPDH gene expression acted as a negative control when qPCR data were processed.…”
Section: Methodsmentioning
confidence: 99%
“…After washing 3 times with 1 × PBS solution, cell samples were harvested with cell scrappers and were sheared with an ultrasonication machine (Scientz 98-III,Ningbo, China). After sonicating for 20 min (pulse 5 sec, interval 5 sec) with 25% power, cell lysate was centrifuged for 10 min at 12,000 rpm; and the resulting supernatant was retained for ChIP assays as described previously ( Zhang et al, 2022 ), where antibodies against TBP (SC-204; Santa Cruz Biotech. ), BRF1 (SC-81405; Santa Cruz Biotech.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation